Microbial diversity and biotechnological potential of mangrove leaf litter in Kebun Raya Mangrove, Surabaya, Indonesia - L. Alifia; E. Zulaika; S. Soeprijanto; A. Hamzah; A. Luqman (Brazilian Journal of Biology)
Abstract Mangrove ecosystems play a crucial role in maintaining ecological balance with leaf litter serving as an important substrate for diverse microbial communities. This study investigates the microbial communities inhabiting leaf litter from four different mangrove species: Rhizophora apiculata, Rhizophora stylosa, Sonneratia caseolaris, and Avicennia marina collected from Kebun Raya Mangrove, Surabaya, Indonesia. Using metagenomic sequencing, we revealed that Proteobacteria were predominant, followed by Chlorobi and Actinobacteria in the samples. Interestingly, we detected notable populations of anaerobic bacteria, including genus of Chlorobaculum and Allochromatium. Metagenomic analyses exhibited high levels of adaptation to stressors, evidenced by the prevalence of genes conferring resistance to antibiotics (e.g., beta-lactams, tetracyclines), heavy metals (e.g., chromium, arsenic), and hydrocarbons. Furthermore, the metagenomic analysis revealed the presence of genes involved in the biosynthesis of polyunsaturated fatty acids (PUFAs), antimicrobial compounds, and plant growth-promoting activities. These findings highlight the potential of mangrove leaf litter as a reservoir of beneficial microbes with diverse biotechnological applications, including bioremediation, nutraceuticals, pharmaceuticals, and agriculture.